Fever of Unknown Origin in Children: The Challenge of History Taking - Testa, S; Faranghi, S; Mazzitelli, S; Beretta, GB; Pietro, G Di; Renisi, G; Petaccia, Antonella (Archives of Case Reports, 2023)
A fever of unknown origin (FUO) in children is usually described as a fever of at least 8 days duration with no apparent diagnosis after initial investigations, including taking medical history and preliminary laboratory assessment. Infectious diseases are the most common cause of FUO, followed by rheumatologic and neoplastic conditions. In this report, we present a case of a 15-year-old Caucasian boy with a silent past medical history, who presented at our Pediatric ER department with a three-day history of fever, fatigue, and abdominal pain with diarrhoea. Initial laboratory testing and microbiological work-up were non-significant. At hospital admission, a broad infectious diagnostic work-up was pursued, including serologies and polymerase-chain-reaction (PCR) for CMV, EBV, HAV, Parvovirus, Toxoplasma gondii and Adenovirus, all negative. Given mild splenomegaly and linfadenopathy, systemic Juvenile Idiopathic Arthritis (s-JIA) was suspected, as well as Multi-inflammatory Syndrome in Children (MIS-C), but the patient did not meet their main diagnostic criteria. Malignancy was ruled out by a negative bone marrow fine-needle aspiration cytology and whole-body PET-CT scan. On hospital day 8, Brucella was identified on a new set of blood cultures and a combined antibiotic therapy was started with IV Gentamicin plus per os Doxycycline. The patient’s general conditions rapidly improved, and both fever and diarrhoea resolved. A reassessment of the patient’s medical history before discharge revealed exposure to unpasteurized soft cheese in the weeks prior to the onset of symptoms. This case underlines the importance of taking a complete medical history, as well as a full diagnostic work-up to unveil unusual infectious etiologies behind FUO. After the preliminary negative microbiological tests, a connective tissue disease was ruled out (i.e. lack of cutaneous or articular involvement), as well as malignancy, which led to a closer evaluation for infection and the diagnosis of Brucellosis.